PARP1 resolves DNA replication defects in PCNA-associated DNA repair disorder - Wang, L (2019)
Proliferating cell nuclear antigen (PCNA) is an essential cofactor for DNA replication and repair. The toroidal structure of a PCNA trimer makes it a sliding clamp protein, which utilizes its interdomain connecting loop (IDCL) interacting with PIP-box containing proteins to recruit these clients to sites of DNA replication to enable their functions. In 2014, the Crosby and Green laboratories reported a novel DNA repair disorder with clinical features including short stature, hearing loss, premature aging, telangiectasia, neurodegeneration, and photosensitivity, which results from a homozygous missense (p.Ser228Ile) alteration of PCNA so it is named PCNA-associated DNA repair disorder (PARD). Previous structural studies have shown that the S228I alteration of PCNA results in a dramatic conformational change of the IDCL, and biochemical studies indicated a profound perturbation of PCNA's interaction with many of its interaction partners, including FEN1, LIG1, Cdt1, DNMT1 and XPG. Patient-derived cells exhibited marked abnormalities in response to UV irradiation, displaying substantial reductions in both UV survival and RNA synthesis recovery. However, no evidence for DNA replication defects has been found in these patient-derived cells. The aim of this thesis was to determine cellular pathways that are affected by the S228I alteration and to uncover mechanisms by which PCNAS228I cells tolerate the perturbed PCNA interactions in specific pathways. An isogenic PCNAS228I knock-in hTERT RPE-1 cell line was generated using CRISPR-Cas9 technique. Phenotypes observed in patient-derived cells were recapitulated in the knock-in cell line. By applying survival assays with treatment of different chemical agents, we showed most DNA repair pathways unaffected, except that PCNAS228I cells were more sensitive to treatment with the PARP inhibitor olaparib than WT controls. By comet assay as well as immunostaining of γH2AX, I showed that olaparib induced more DNA damage in cells with the PCNAS228I alteration, and FACS analysis showed perturbed cell cycle progression after PARP inhibition. By using an inhibitor of PARG, I detected high levels of PAR chains being formed at replication forks in PCNAS228I cells. Thus I proposed that the PCNAS228I mutation results in abnormal interactions between PCNA and key enzymes needed for normal Okazaki fragment maturation at replication forks. The resultant persistent single-strand breaks are processed via a back-up, PARP-dependent mechanism to ensure completion of lagging strand synthesis. Overall, these data have implications both for the etiology of PCNA-associated repair disorder as well as suggesting novel circumstances in which PARP-inhibition might be of use in the cancer clinic.